Dilution and microfiltration of particulate corticosteroids for spinal epidural injections: impact on drug concentration and agglomerate formation. (22nd June 2019) - Alcántara Guardado, A.; Cooper, G.; Weightman, A.; Spiess, R.; Baker, A.D.L.
Summary: Particulate corticosteroids have been described to lead to greater pain improvement compared with their non‐particulate counterparts when used in epidural injections. It is hypothesised that filtering may significantly impact their concentration and long‐term efficacy. We investigated if passing particulate suspensions through different commonly‐used filters affects drug dosage. Two particulate corticosteroid formulations, triamcinolone acetonide and methylprednisolone acetate, were mixed at different concentrations with either bupivacaine hydrochloride or 0.9% sodium chloride. Solutions were passed through a 5‐μm and a 0.2‐μm filter. Mass spectroscopy results indicated a complete loss of corticosteroid from the solutions using both filters, and light microscopy imaging demonstrated agglomerate formation, suggesting that filtering interferes with drug dosage. The choice of diluents must also be considered to reduce large agglomerate formation. Clinicians should be aware of the consequences of filtering particulate suspensions and carefully consider the selection of diluent when considering treatment plans.